2013
DOI: 10.1093/llc/fqt025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the inter-method reliability and correlational validity of the Body Type Dictionary

Abstract: The political negotiation, erection and fall of national and cultural borders represents an issue that frequently occupies the media. Given the historical importance of boundaries as a marker of cultural identity, as well as their function to separate and unite people, the Body Type (BTD) (Wilson 2006) Dictionary represents a suitable computerized content analysis measure to analyse vocabulary qualified to measure body boundaries and their penetrability. Out of this context, this study aimed to assess the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
(37 reference statements)
0
10
1
Order By: Relevance
“…Empirical research has also identified a relationship between body boundary awareness and primordial thought by measuring body boundary imagery and regressive language in personal memories, thus providing some supporting evidence for the Freudian theory that assumes that the body, unconscious thought and language represent interrelated concepts (Cariola, 2014).…”
Section: Body Boundaries and Primordial Mental Activitymentioning
confidence: 85%
“…Empirical research has also identified a relationship between body boundary awareness and primordial thought by measuring body boundary imagery and regressive language in personal memories, thus providing some supporting evidence for the Freudian theory that assumes that the body, unconscious thought and language represent interrelated concepts (Cariola, 2014).…”
Section: Body Boundaries and Primordial Mental Activitymentioning
confidence: 85%
“…The Body Type Dictionary (BTD) (Wilson, 2006;Cariola, 2014aCariola, , 2014b) is a reliable and valid computerised dictionary that calculates the frequency of semantic items categorised as barrier imagery or penetration imagery, based on Fisher and Cleveland's (1958) scoring system. The BTD contains 551 words for barrier imagery, 231 words for penetration imagery, and 70 exception words that prevent the erroneous matching of ambiguous word stems that are assigned to 12 semantic categories.…”
Section: Content Analysismentioning
confidence: 99%
“…This reduction in barrier imagery in High Barrier patients might be indicative of the empathic and nonjudgmental therapeutic alliance enabling patients to explore and reflect upon their emotions and thoughts, such as anxieties and traumatic experiences. This exploration and reflection may have resulted in a lower encapsulating body boundary and muscular sensitivity associated with a conditioned punishment-reward response (Cariola, 2014a). A reduced body boundary enables a functional self-other differentiation, facilitating patients' ability to acknowledge their feelings and to be reliant on their own value judgments, concurrent with a greater capacity to trust others.…”
mentioning
confidence: 99%
“…The Body Type Dictionary (Wilson, 2006) represents a valid and reliable computerised scoring system that measures the lexical frequencies of barrier and penetration imagery as outlined by Fisher and Cleveland's manual body boundary scoring system (Cariola, 2013). The BTD contains 599 barrier imagery words, 252 penetration imagery words, and 70 exception words, which prevent the erroneous matching of ambiguous word stems assigned to 12 semantic categories.…”
Section: Body Type Dictionarymentioning
confidence: 99%
“…Empirical research has demonstrated that both penetration and barrier imagery increase with the level of regressive cognition, which indicates that barrier and penetration imagery reflect the different psychological functions of phenomena related to regressive cognition (Cariola, 2013). Primordial thought language has been measured using the Regressive Imagery Dictionary (RID) (Martindale, 1975(Martindale, , 1990), which gauges the frequency of lexical items classified as primordial thought language and conceptual thought language.…”
Section: Body Type Dictionarymentioning
confidence: 99%